2010
DOI: 10.2478/v10042-009-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Xenoestrogens diethylstilbestrol and zearalenone negatively influence pubertal rat's testis.

Abstract: Abstract:The aim of this study was to assess the impact of xenoestrogens: diethylstilbestrol (DES) and zearalenone (ZEA) on rat's pubertal testis and to compare it with the effect of natural estrogen -17β-estradiol (E). Male Wistar rats were daily, subcutaneously injected at 5 th -15 th postnatal days (p.d.) with E (1.25 or 12.5 μg) or DES (1.25 or 12.5 μg) or ZEA (4 or 40 μg) or vehicle. At 16 th p.d. testes were dissected, weighted, and paraffin embedded. Following parameters were assessed: diameter and leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…The autopsy was performed on the 16 th pd to observe the possible disturbances caused by DBP within a short time following treatment. Such rapid disruptive actions have previously been observed for different xenoestrogens [8] and hormones [20]. All the sacrificed animals were weighed.…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations
“…The autopsy was performed on the 16 th pd to observe the possible disturbances caused by DBP within a short time following treatment. Such rapid disruptive actions have previously been observed for different xenoestrogens [8] and hormones [20]. All the sacrificed animals were weighed.…”
Section: Methodsmentioning
confidence: 72%
“…Neither testis weight and morphology, nor testosterone, estradiol or FSH serum levels were affected. In the same study model, 17b-estradiol, diethylstilbestrol (DES) and zearalenone (ZEA) showed a negative impact on testicular development even when administered in lower doses [8]. The majority of reports on DBP's influence on the male reproductive tract describe treatment with doses of around 500 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative effect was observed even in men of the F2 generation whose fathers had been exposed to DES in utero [176]. The adverse effect of DES on male fertility was also proven in rats [177] and mice [178,179]. One possible mechanism was suggested in a study showing that the neonatal DES exposure induced alterations in the DNA methylation status of seminal vesicle secretory protein IV (Svs4) and lactoferrin (Ltf) genes in seminal vesicles of adult mice [180].…”
Section: Interaction Of Oestrogen-like Compounds With Ersmentioning
confidence: 99%